Premodern Popular Culture: Between Democratization and Marginalization - Foletti, Ivan; Frantová, Zuzana; Palladino, Adrien (Eikón / Imago, 2022)
Leader article of Pre-Modern “Pop Cultures”? Images and Objects Around the Mediterranean (350-1918 CE). The aim of this monography is to analyze, from the most significant images and objects, to the traditions that have accompanied us to this day.